THE EFFECT OF PRODUCT SELLING PRICES ON PROFITABILITY AT PT. SEMEN BOSOWA IN MAROS DISTRICT - Hikma Niar (International Conference on Social and Islamic Studies, 2021)
This study aims to determine the effect of product selling price on profitability at PT. Semen Bosowa in Maros regency which is descriptive and comparative with the entire population of data in the form of income statements and production data at PT. Semen Bosowa in Maros Regency. Sampling was carried out by means of positive sampling in order to obtain a sample of the income statement and production data for the years 2015-2019. Data were analyzed using simple linear regression analysis, correlation coefficient and t test. The result of regression analysis shows that Ŷ = 0.204 - 0.020X. This equation means that the constant value of 0.204 is the amount of profitability achieved regardless of the level of the selling price. The regression coefficient value is -0.020 which means that if the selling price increases by 1 percent, it will cause a decrease in the value of profitability at PT. Semen Bosowa in Maros Regency of 0.020. This explains the direction of the negative coefficient between selling price and profitability, namely when the selling price increases it will cause a decrease in profitability. This means that the selling price has an effect but not significantly on profitability.